Tara! chika tayo sa parlor : narratives of the lived communication systems of the parloristang bakla subgroup inside the beauty parlor - Manongsong, Charvin Jules Albunag 1998-
Communication is essential in the creation of an individual identity and the creation of the sense of a community. Thus, to understand the distinctiveness of a group and a community, the exploration of the holistic communication is necessary. Groups create a communication system that is distinction that separates groups from one another. These systems are the structures of interdependent and interactive aspects (motivations for information, message influences, communication practices, nature of relationships, and external cultural contexts) of the communication process that creates a common goal and a deeper commitment. Entwined within Filipino society is the country's unique kabaklaan which is one of the most discriminated minorities in the country. These give rise to the question: What are the narratives of the lived communication system of the parloristang bakla subgroups at urban poor Filipino beauty parlors? The study generally aims to understand the different aspects of the lived communication systems of the parloristang bakla subgroup. The study integrated the Systems Theory (von Bertalanffy, 1968), the Situated Mental Construction of Social Reality (Langlotz, 1972), and the Communication Theory of Identity (Hecht, 1993) as its guide and theoretical anchors. Furthermore, an interpretive research paradigm was utilized through a multi-method approach composed of interviews, focused groups discussions, and participant observations. The informants are two beauty parlor-based groups located in Quezon City, Philippines whose members mostly identify as bakla sampled through non-probability, purposive snowball sampling. The data-gathering period lasted within the duration of six weeks (9 March 2019 to 15 April 2019). Results revealed that the beauty parlor communication system is a unique and native communication system that is both filial and professional in nature. This system is created through the congregation of the parloristas' responses to satisfy their physical, psychological, and emotional desires. Conversations are unrestricted characterized by the open communication of all topics, even those considered as taboo and unusual in Philippine society. These messages are almost always forwarded in humorous modes. Furthermore, the communication practice of the batuhan ng mga biro is unique to the beauty parlor. Other communication practices reveal the parlorista groups' identity of kasiyahan, kamalayan, kaalaman, kagandahan, and kalingkutan. Their interdependent relationships are managed and maintained through relational dialectics. Networks and authorities are dynamic and reliant on the variations in the groups' message influences that also reflect their communication practices. Furthermore, external cultural contexts (the groups' situation in their communities; and relationship with customers, and neighboring households and establishments) serve as a form of individual validation and an extension of the beauty parlor group. In sum, the beauty parlor communication system is essential in the understanding of the parloristang bakla subgroup and the exploration of their identities. The beauty parlor communication system is colorful and as unique as the parloristang identity.